Pengelolaan Limbah Obat dalam Rumah Tangga - Tasya Nadia Putri; Winda Trijayanthi Utama (Medula, 2022)
Environmental pollution caused by drug waste has become a global concern because it can reduce the quality of human life. Based on Riskesdas 2018, 35.2% of households store drugs for self-medication. Drug waste is estimated to increase along with the population growth rate, followed by increased consumption of drugs in the community. Drug waste includes unused and expired drugs. Household drug waste is usually disposed of directly into landfills, so it has the potential to cause various problems in the environment, including damage to water, air, and soil, ecosystems, toxins for animals and humans. This article aims to determine the management of pharmaceutical waste in the household so that it does not cause negative impacts on health and the environment. The method of writing this article with a literature review is to analyze the management of drug waste in the household. Most people do not know the proper management of drug waste. Drug waste is disposed of without paying attention to the drug waste management system. The community is expected to be able to implement the management of drug waste in households to prevent environmental pollution that can reduce the quality of life.